2021
DOI: 10.21608/ejh.2021.59941.1425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Energy Drink on the Pancreas of Adult Male Albino Rat and the Possible Protective Role of Avocado Oil. Histological and Immunohistochemical Study

Abstract: Introduction: Energy drinks are widely used among youth as boosters to increase their concentration. Many Health disorders are associated with energy drinks. Avocado oil is a natural oil extracted from avocado fruit and possess an antioxidant and anti-inflammatory effects. Aim of the Work: This work was conducted to investigate the effect of energy drink on the histological structure of the pancreas of adult male albino rat and to evaluate the possible protective role of avocado oil. Materials and Methods: For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Abonar et al [ 125 ], Rehman et al [ 126 ], and Haroun et al [ 127 ] investigated the effect of energy drinks on the pancreas of adult male albino rats. They performed histological, immunohistochemical and biochemical studies that revealed alterations in pancreatic cytoarchitecture.…”
Section: Discussionmentioning
confidence: 99%
“…Abonar et al [ 125 ], Rehman et al [ 126 ], and Haroun et al [ 127 ] investigated the effect of energy drinks on the pancreas of adult male albino rats. They performed histological, immunohistochemical and biochemical studies that revealed alterations in pancreatic cytoarchitecture.…”
Section: Discussionmentioning
confidence: 99%